¿Quién debe ser el guardián de la Constitución? : una lectura del debate entre Kelsen y Schmitt a la luz del caso Prusia contra Reich de 1932 - Vita, Leticia (2017)
This article seeks to rethink the classic debate between Carl Schmitt and Hans Kelsen on the defense of the Constitution in the light of the court case known as -Prussia against Reich-, heard before the High Court in Leipzig, Germany, in 1932. This case, which involved Schmitt as defense lawyer of the Reich; Hermann Heller who represented the Social Democrats in Prussia; and which ruling was commented by Kelsen; allows as to test the ideas on who should be the defender of the Constitution in a crucial case for Weimar Republic's fate, and enables us to add a third voice to the debate: Heller's one.